The influence of negative life events on college students’ suicidal ideation: the mediating role of entity theory and the moderating role of meaning in life - Liu, Dan; Geng, Xiaowei; Zhang, Fuwei; Zhang, Yuan; Li, Xueli (Frontiers in Psychology, 2024)
Suicidal ideation is a desire, thought or conception that is closely associated with suicide, which is an important risk factor of suicidal behaviors. Negative life events could impact college students' suicidal ideation. According to the suicide susceptibility-stress model, the interaction of susceptibility factors and stressors can influence college students' suicidal ideation. The present study investigated the role of entity theory and meaning in life in the influence of negative life events on college students' suicidal ideation. A nationwide questionnaire survey was conducted among 938 college students. The Beck Scale for Suicide Ideation Scale, the Implicit Personality Theory Questionnaire, the Adolescent Life Events Scale, and the Meaning in Life Questionnaire were used. Results showed that negative life events were positively correlated with suicidal ideation, entity theory played a mediating role and meaning in life moderated the mediation of entity theory. To sum up, meaning in life and entity theory may bring some benefits to college students, that is, when facing negative life events, meaning in life and entity theory can attenuate students' suicidal ideation.